Regulation of rat hepatic 3 alpha-hydroxysteroid dehydrogenase in vivo and in primary cultures of rat hepatocytes. - R T Stravitz; Z R Vlahcevic; W M Pandak; A Stolz; P B Hylemon (Journal of Lipid Research, 1994)
In the bile acid biosynthetic pathways of humans and the rat, hepatic 3 alpha-hydroxysteroid dehydrogenase (3 alpha-HSDH) catalyzes the stereospecific reduction of the 3-oxo group of bile acid precursors. In addition, 3 alpha-HSDH may serve to shuttle bile acids from sinusoidal to apical (cannalicular) membranes of the rat hepatocyte. The objective of the present study was to define the molecular regulation of rat hepatic 3 alpha-HSDH in response to the key effectors of cholesterol 7 alpha-hydroxylase, the rate-determining enzyme in bile acid biosynthesis. Steady-state 3 alpha-HSDH mRNA levels in primary cultures of rat hepatocytes fell to 16 +/- 1% of whole liver levels after 72 h in culture, indicating that the gene is not spontaneously expressed in isolated hepatocytes. However, the addition of thyroxine (1.0 microM) or dexamethasone (1.0 microM) to the culture medium resulted in steady-state mRNA levels of 34 +/- 4% and 102 +/- 20% of whole liver levels, respectively. Moreover, the combination of thyroxine and dexamethasone (each 1.0 microM) induced mRNA to levels 2-fold higher than whole liver. 3 alpha-HSDH specific activity in cultured hepatocyte cytosol increased from 3.0 +/- 0.7 to 10.4 +/- 1.3 nmol/min per mg protein in no-addition and thyroxine plus dexamethasone-treated cultures, respectively; protein mass underwent similar changes. Whole liver 3 alpha-HSDH mRNA levels decreased in thyroidectomized, adrenalectomized, and hypophysectomized rats, to 60 +/- 6%, 51 +/- 4%, and 29 +/- 5% of sham-operated rats, respectively.(ABSTRACT TRUNCATED AT 250 WORDS)